2019
DOI: 10.1093/ntr/ntz123
|View full text |Cite|
|
Sign up to set email alerts
|

Do Local Tobacco-21 Laws Reduce Smoking Among 18 to 20 Year-Olds?

Abstract: Introduction States and municipalities are increasingly restricting tobacco sales to those under age 21, in an effort to reduce youth and young adult smoking. However, the effectiveness of such policies remains unclear, particularly when implemented locally. Methods Analyses use 2011–2016 data from the Behavioral Risk Factor Surveillance System’s Selected Metropolitan/Micropolitan Area Risk Trends dataset. Difference-in-diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…Studies suggest that earlier state and local Tobacco 21 policies reduced smoking among individuals aged 18−20 years. 10,11 Thus, assuming necessary compliance and enforcement efforts, the federal Tobacco 21 law offers a promising means to reduce youth nicotine exposure.…”
Section: Regulatory Challenges and Opportunitiesmentioning
confidence: 99%
“…Studies suggest that earlier state and local Tobacco 21 policies reduced smoking among individuals aged 18−20 years. 10,11 Thus, assuming necessary compliance and enforcement efforts, the federal Tobacco 21 law offers a promising means to reduce youth nicotine exposure.…”
Section: Regulatory Challenges and Opportunitiesmentioning
confidence: 99%
“…Previous empirical studies evaluating local T21 policies provided mixed evidence. While some studies have found that implementation of local T21 policies was associated with reductions in smoking prevalence among adolescents and young adults,19 20 another study on New York City T21 failed to find such an association 21. One potential reason for the mixed findings is increased cross-border cigarette purchasing, which could be an unintended consequence of local T21 policies.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, state-level cannabis policies in the United States have aimed to liberalize the accessibility of cannabis products, though there have been few state-level prevention campaigns. Using national surveillance data across states has been the standard approach to evaluate the effects of these policies on youth and young adult perceptions and behaviors [ 6 , 7 ]. These evaluations, which use cross-sectional data over time, may mask more nuanced trends in individual-level changes in harm perceptions and behavior and have largely failed to address spillover effects on other substance use.…”
Section: Introductionmentioning
confidence: 99%